Fatigue life enhancement via residual stress engineering due to local forming during refill friction stir spot welding - Becker, Niklaas; Kuhn, Daniel; Piochowiak, Jan; Klusemann, Benjamin (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Refill friction stir spot welding is a promising joining process in lightweight design. As lightweight structures react sensitively to cyclic loads, the fatigue life of the joints are of particular interest. In previous studies, attempts have been made to optimize the fatigue properties based on process parameter modification albeit with moderate success. The introduction of post-processing steps such as laser-shock or hammer peening resulted in an improvement but also in a considerable higher effort. In this work, a new approach is pursued, namely to increase the fatigue life properties by manipulating the residual stresses already during the welding process. This is achieved by milling a pocket into one of the joining surfaces prior to the welding process. The pocket and the clamping forces that occur during the welding process cause an elongation of the material. After releasing the clamping force, the elastic springback effect causes compressive forces, leading to compressive residual stresses in the spot weld. This has made it possible to increase the endurance limit for shear-loaded samples by a factor of 40 and for cross-tension-loaded samples by a factor of 18.
Keywords: Refill Friction Stir Spot Welding; Fatigue Life; Residual Stress